THE EFFECT OF REMUNERATION ON MOTIVATION THAT IMPLICATES EMPLOYEE’S PERFORMANCE IN XYZ COMPANY - Aldi Cahyanugroho; Musa Hubeis; Hari Wijayanto (School of Business, IPB University (SB-IPB), 2016)
PT XYZ is foreign investment company on food and beverages manufacturer with health benefit positioning. PT XYZ is willing to consistent of safety, quality and productivity (SQP) aspect, therefore should be encouraged by high quality human resources. Employee motivation was stimulated by remuneration program in order to increase employee performance in PT XYZ. The aim of this study was to analyze remuneration effect towards employee motivation and it’s implication to employee performance at PT XYZ using employee perception. The population of this study is taken from staff level to supervisor level from 10 Departments. The numbers of sample are 132 people. The sampling technique used in the study was stratified with purposive and convenience sampling method with the analytical method using Structural Equation Modeling (SEM). The result of this study shows remuneration has significant effect towards employee motivation and employee performance, while motivation has insignificant effect towards employee performance. SEM results show each highest coefficient are wages based on needs indicator at remuneration variable, individual development indicator at variable motivation and obedience indicator at employee performance variable. Management of PT XYZ should be maintaining components of remuneration, motivation and employee performance that’s already had good score and also pay attention to component of remuneration which has low score index to enhance employee motivation and also employee performance.Keywords: employee motivation, employee performance, remuneration, SEM